Corrosion Behavior of Mild Steel in Various Environments Including CO2, H2S, and Their Combinations - Yuanguang Yue; Zhibiao Yin; Shiming Li; Ziyue Zhang; Qifu Zhang (Metals)
This paper investigates the corrosion behavior of mild steel in simulated oilfield wastewater under CO2, H2S, and their mixture. Using the electrical resistance method, the corrosion rates were monitored, and the influence of corrosion product films on overall performance was analyzed. The results show that the CO2/H2S mixture causes the highest corrosion rate. Metallographic examination and X-ray diffraction (XRD) provided insights into the nature of the corrosion products formed on the steel surface. While hydrogen sulfide (H2S) does not prevent general corrosion, it plays a role in mitigating localized damage. Corrosion leads to deep, narrow pits that weaken the structural integrity without significant surface damage, making it more dangerous than uniform corrosion. In CO2-only environments, electrochemical reactions form protective oxide layers. However, H2S alters this process by forming iron sulfides (FeS), which are less protective but still act as a barrier against further corrosion. In mixed CO2/H2S environments, interactions between the gases complicate the corrosion dynamics, increasing medium aggressiveness and accelerating material degradation. Understanding these mechanisms is critical for the petroleum industry, where equipment is exposed to harsh conditions with varying CO2 and H2S concentrations. Recognizing the dual role of H2S—its inability to inhibit general corrosion but its effectiveness in reducing pitting—can guide material selection and inhibitor development. This knowledge enhances the durability and safety of oil and gas infrastructure by addressing the most damaging forms of corrosion.